Observations of vertical mixing in autumn and its effect on the autumn phytoplankton bloom. (October 2019) - Wihsgott, Juliane U.; Sharples, Jonathan; Hopkins, Joanne E.; Woodward, E. Malcolm S.; Hull, Tom; Greenwood, Naomi; Sivyer, David B.
Highlights: New, high-resolution observations of full seasonal cycle in a temperate shelf sea. Wind mixing is primary control on mixed layer depth. Mixed layer deepening fuels autumn phytoplankton bloom. Critical depth hypothesis predicts shutdown of primary production in autumn. Autumn bloom can act as significant contributor to seasonal drawdown of carbon. Abstract: This work examines the seasonal cycle of vertical density structure and its influence on primary production in a temperate shelf sea, with a particular focus on the breakdown of stratification in autumn. We do this by combining new, high resolution observations of water column structure, meteorological forcing, nitrate and chlorophyll fluorescence collected between March 2014 and July 2015 on the North West European Shelf. Our results challenge the generally accepted assumption that convection dominates over wind driven mixing resulting in seasonal breakdown of stratification. Furthermore we found, that vertical mixing in autumn not only transformed the vertical density structure but also the vertical structure of chlorophyll biomass and surface nutrients. The subsurface chlorophyll maximum was eroded and a vertically homogeneous profile of chlorophyll biomass established itself above the pycnocline. This increased mixing also led to replenishment of surface nitrate concentrations, which supported an autumn phytoplankton bloom. While the significance of phytoplankton blooms in autumn has previously not been well quantified, we argue that these can act as a significant contributor to the seasonal drawdown of carbon.